TIAGO F. CARRIJO, RUDOLF H. SCHEFFRAHN & JAN KŘEČEK (2015) Compositermes bani sp.n. (Isoptera, Termitidae, Apicotermitinae), a new species of soldierless termite from Bolivia. Zootaxa, 3941(2): 294–298. - Carrijo, Tiago F.; Scheffrahn, Rudolf H.; Křeček, Jan (Zootaxa, 2016)
N/A